2020
DOI: 10.51791/njap.v44i4.490
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional potential of (dc.) Hochst. pods in the semi-arid zone of Nigeria

Abstract: ThestudywasconductedtoevaluatethenutritivevaluesofPiliostigmareticulatumpodsfrom field grown stands within the semi-arid zone of Nigeria. 250 fruiting trees from five locations within coordinates of longitude 11 42' to 12 27' and latitude 07 29' to 11 04' with 50 stands per location were monitored up to pod maturity to 80% dried pods. The harvested pods were sampled and bulked in 50kg jute bag per location and analyzed for nutritive values, antinutritional factors (ANFs), macro-and micro-minerals.Multi-stage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
1
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
1
2
1
2
Order By: Relevance
“…Whereas; T8 and T3 were the least in Mg, Ca and Na. The mineral contents evaluated were higher than the values reported by Abdurrahaman et al, (2018a) for Gamba mixed with three tropical legumes forages (Groundnut, Watermelon and Cowpea) This showed that feeding of these silages may not require macro minerals supplementation.…”
Section: Mineral Contents Of the Prepared Silagescontrasting
confidence: 52%
See 2 more Smart Citations
“…Whereas; T8 and T3 were the least in Mg, Ca and Na. The mineral contents evaluated were higher than the values reported by Abdurrahaman et al, (2018a) for Gamba mixed with three tropical legumes forages (Groundnut, Watermelon and Cowpea) This showed that feeding of these silages may not require macro minerals supplementation.…”
Section: Mineral Contents Of the Prepared Silagescontrasting
confidence: 52%
“…The crude protein of the resultant silages met the protein requirement for small ruminant production (Abdurrahaman et al, 2017).…”
Section: Results and Discussion Ph Colour And Aroma Of The Prepared S...mentioning
confidence: 98%
See 1 more Smart Citation
“…La valeur obtenue par Sanou et al (2010) sur des échantillons récoltés dans la zone Nord soudanienne du Burkina Faso, est également inférieure à celle de l'essai 2 (217 vs 79 g/kg MS). Mais Abdurrahaman et al (2018) ont obtenu dans la zone semi-aride du Nigéria.une valeur maximale en PB assez proche des résultats de l'essai 2 (194,6 vs 217g/kg MS. De même, les teneurs en NDF et ADF sont inférieures aux valeurs de l'essai 1 et à celles obtenues par Sanou et al (2010) (NDF: 298 vs 543 g/kg MS, ADF: 221 vs 399 g/kg MS). Abdurrahaman (2018) aussi a obtenu des valeurs en fibres supérieures situées dans la plage de variation de 462 à 532 g/kg MS pour NDF et de 369 à 405 g/kg MS pour ADF sur des échantillons de gousses prélevés sur plus de 200 pieds de P. reticulatumnos.…”
Section: Discussionunclassified
“…Mais Abdurrahaman et al (2018) ont obtenu dans la zone semi-aride du Nigéria.une valeur maximale en PB assez proche des résultats de l'essai 2 (194,6 vs 217g/kg MS. De même, les teneurs en NDF et ADF sont inférieures aux valeurs de l'essai 1 et à celles obtenues par Sanou et al (2010) (NDF: 298 vs 543 g/kg MS, ADF: 221 vs 399 g/kg MS). Abdurrahaman (2018) aussi a obtenu des valeurs en fibres supérieures situées dans la plage de variation de 462 à 532 g/kg MS pour NDF et de 369 à 405 g/kg MS pour ADF sur des échantillons de gousses prélevés sur plus de 200 pieds de P. reticulatumnos. Les facteurs en cause de ces différences sont à mettre en rapport avec le type de sol et la pluviométrie (la localisation), l'âge de la plante et la saison.…”
Section: Discussionunclassified